Rocatinlimab Improves Patient-Reported Outcomes in Adults with Moderate-to-Severe Atopic Dermatitis: Results from a Double-Blind Placebo-Controlled Phase 2b Study - Gooderham, Melinda; Guttman-Yassky, Emma; Igawa, Ken; Kabashima, Kenji; Esfandiari, Ehsanollah; Rylands, Angela J.; Williams, Angela; Nixon, Annabel; Dent, Jennifer E.; Simpson, Eric (Dermatology and therapy, 2024)
Introduction In adults with moderate-to-severe atopic dermatitis (AD), rocatinlimab demonstrated significant and progressive improvement in clinical measures of disease severity compared with placebo. This post hoc analysis of a phase 2b study was undertaken to understand the disease burden and to assess the impact of rocatinlimab on patient-reported outcomes (PROs). Methods This analysis used baseline data from a multicenter, randomized, double-blind study of adults with moderate-to-severe AD, who completed a Worst Pruritus numerical rating scale (NRS), Sleep Disturbance NRS, and the Dermatology Life Quality Index (DLQI). A mixed model for repeated measures was used to estimate changes in PRO scores from baseline; scores were also compared with clinically meaningful change benchmarks. Results The analysis included 267 subjects, mean (SD) age 37.9 (14.7) years, 40.8% female; 55.1% grade 3 and 44.9% grade 4 Investigator Global Assessment for AD. Mean (SD) scores were: Worst Pruritus NRS 7.5 (1.9), Sleep Disturbance NRS 5.5 (2.9), DLQI total score 12.6 (7.1). Worst Pruritus and Sleep NRS scores had low positive correlations with SCORing AD (SCORAD) score ( r = 0.44, r = 0.45 respectively) and negligible correlations with Eczema Area and Severity Index (EASI) score and area affected ( r < 0.30). DLQI score varied by sex, study country, race, age, longer disease duration, disease severity (EASI and SCORAD), presence of asthma, and Worst Pruritus NRS, Sleep disturbance NRS, and DLQI scores. Rocatinlimab showed benefit on all three PROs, with significant improvements from baseline at the end of the double-blind period (week 18) and active treatment extension (week 36). Benefits were maintained over 20 weeks’ post-treatment follow-up. The benefit of rocatinlimab treatment on PROs is rapid and maintained for at least 20 weeks following treatment completion. Conclusion This analysis demonstrates the importance of characterizing the burden of moderate-to-severe AD from the patient’s perspective, alongside clinical disease measures, to develop a fuller picture of treatment benefit. Trial Registration ClinicalTrials.gov identifier, NCT03703102.